A Comparative Study of the Values of Ionization Constants for Acid Compounds Derived from N-formyl pipyidines - Adel Azzouz; Heba El Mawla (College of Education for Pure Sciences, 2012)
Abstract The paper is concerned with the determination of pKa or pK'a values for a new fourteen imines by potentometric titration method. These imines are prepared from the mother compound the N- formyl pipyidines in a forms of oximes, phenolic Schiff bases, amino Schiff bases and others. Most of these imines are acids and their pKa values are determined by titration with 0.1M NaOH. The other imines are Schiff bases and their pK'a values for their nitrilium ions are similarly determined by titration with 0.1M HCl. Finally, the paper led to a comparison of pKa or pK'a values for the similar imines in the study, either in forms of oximes, phenolic Schiff bases, amino Schiff bases and others.